Early 21st-century Serbian exploitation cinema - Pająk, Patrycjusz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
Exploitation films are one of the main trends of the Serbian cinema of the beginning of the 21st century, when Serbia enters the second phase of systemic transformation, striving to neutralize the effects of the crisis in the first phase of transformation – towards the end of the 20th century – due to the authoritarian policy of Slobodan Milošević and Yugoslav wars. This non-film context allows better understanding of the phenomenon of these films, which in many respects are a continuation of the cinema of self-balkanization cultivated in the 1990s, and at the same time differ from it, because they do not offer a compromise with difficult transformational reality, but express the need to release the social trauma born of experience of political violence in the Milošević era.